2001
DOI: 10.1182/blood.v97.7.1925
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the fractalkine receptor CX3CR1 as a genetic risk factor for coronary artery disease

Abstract: Coronary atherosclerosis is a major cause of death in industrialized countries. Monocytes, which play a key role in atherosclerosis, migrate into the vessel wall, presumably guided by specific chemoattractant and adhesion molecules. A compelling candidate for this role is the chemokine receptor CX3CR1, which is expressed on monocytes and acts as either a chemotactic receptor or an adhesion molecule, depending on whether its ligand, fractalkine, is presented free or membrane bound. A common variant of CX3CR1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
275
5
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(298 citation statements)
references
References 10 publications
16
275
5
2
Order By: Relevance
“…14 Clinical cohorts have shown that 2 single nucleotide polymorphisms of CX 3 CR1, V249I and T280M, are associated with reduced prevalence of atherosclerosis and coronary artery disease. 8,9 In addition, the M280 allele is associated with a reduced risk of internal carotid artery (ICA) occlusive disease. 10 Our laboratory has shown that the protein encoded by the M280 allele has impaired adhesive capacity, 7 suggesting that cell adhesion is an important mechanism by which CX 3 CR1 exerts its effect on recruiting cells during vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Clinical cohorts have shown that 2 single nucleotide polymorphisms of CX 3 CR1, V249I and T280M, are associated with reduced prevalence of atherosclerosis and coronary artery disease. 8,9 In addition, the M280 allele is associated with a reduced risk of internal carotid artery (ICA) occlusive disease. 10 Our laboratory has shown that the protein encoded by the M280 allele has impaired adhesive capacity, 7 suggesting that cell adhesion is an important mechanism by which CX 3 CR1 exerts its effect on recruiting cells during vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 CX 3 CL1-deficient mice have a reduction in atherosclerotic plaque burden in the innominate artery. 6 In humans, the V249I/T280M variant of CX 3 CR1 is associated with protection from coronary artery disease [7][8][9] and internal carotid artery occlusive disease. 10 While CX 3 CR1 and CX 3 CL1 are emerging as important mediators of vascular disease, the specific mechanisms regulating their involvement remain unclear.…”
mentioning
confidence: 99%
“…24,25 Fractalkine gene knockout mice have no obvious defects in leukocyte trafficking but are less susceptible to cerebral ischemiareperfusion injury. 26,27 Further evidence for a possible role of fractalkine in cardiovascular disease has come from recent observations in human subjects suggesting that a single amino acid polymorphism at position 249 of the CX 3 CR1 receptor is an independent risk factor for coronary artery disease 28,29 (reviewed by Alexander 30 ). However, the biological rationale for these observations remains unclear Accordingly, we investigated the presence of fractalkine and its cognate receptor, CX 3 CR1, in human coronary artery atherosclerotic plaques.…”
mentioning
confidence: 99%
“…We identified two common single-nucleotide polymorphisms (SNPs), known as V249I and T280M, in the open reading frame of the chemokine receptor CX3CR1 gene. 19 The common CX3CR1-I249 allele and its genetically linked partner, the CX3CR1-M280 allele, are associated with a reduced risk of cardiovascular diseases 20,21 and inflammatory lung disorders. 22,23 CX3CR1 is thus another plausible link between inflammation, airway remodelling and asthma.…”
Section: Introductionmentioning
confidence: 99%